A participatory process to build the competence profile of teachers in a network of Higher Education Institutions in the Latin America context - Pier Giuseppe Ellerani; Mª José Gil Mendoza; Luciano Fiorese (Universitat Politècnica de València, 2012)
This paper presents the experience carried out by a confederation of Higher Education Institution (IUS) operating in six states of Latin America. To achieve the goal of new model of teaching and learning based on "learning process" and shift the paradigm of learning as "centered teaching", the Higher Education Institution have defined a new profile of the university teachers. This action expresses three characteristics presented in this paper: the first refers at the profile as "product" of a Community of Thought; the second refers to "participated process", a working model that allowed the co-construction of the profile with the teachers, the administrative and the human resources staff of the universities; the third presents the tools and technologies used in integrated way (Virtual Collaborative Learning Environment based on Web 2.0, the human resource Management, video-research, e-portfolio). The project - developed by action-research - has defined a shared idea of teaching´ quality, researchbased and supported by tools that allow self-assessment of every teachers, to monitor the quality of universities, to develop plans of continuous improvement building a community of learning. There are presented some qualitative and quantitative data of research.